Hypothalamus-Pituitary-Adrenal Dysfunction in Cholestatic Liver Disease - Petrescu, Anca D.; Kain, Jessica; Liere, Victoria; Heavener, Trace; DeMorrow, Sharon (Frontiers in Endocrinology, 2018)
The Hypothalamic-Pituitary-Adrenal (HPA) axis has an important role in maintaining the physiological homeostasis in relation to external and internal stimuli. The HPA axis dysfunctions were extensively studied in neuroendocrine disorders such as depression and chronic fatigue syndrome but less so in hepatic cholestasis, cirrhosis or other liver diseases. The HPA axis controls many functions of the liver through neuroendocrine forward signaling pathways as well as negative feedback mechanisms, in health and disease. This review describes cell and molecular mechanisms of liver and HPA axis physiology and pathology. Evidence is presented from clinical and experimental model studies, demonstrating that dysfunctions of HPA axis are correlated with liver cholestatic disorders. The functional interactions of HPA axis with the liver and immune system in cases of bacterial and viral infections are also discussed. Proinflammatory cytokines stimulate glucocorticoid (GC) release by adrenals but they also inhibit bile acid (BA) efflux from liver. Chronic hepatic inflammation leads to cholestasis and impaired GC metabolism in the liver, so that HPA axis becomes depressed. Recently discovered interactions of GC with self-oscillating transcription factors that generate circadian rhythms of gene expression in brain and liver, in the context of GC replacement therapies, are also outlined.